The role of new media financial news in the development of China's financial industry - Ruan, Qijie; Wan Abas, Wan Anita; Hassan, Abd Rauf (Human Resource Management Academic Research Society, 2023)
This paper introduces the institutional role of Chinese financial news in the process of financial deepening. This article analyzes popular articles on Sina Finance to study how mainstream financial news chooses to cover the types and topics of "Internet finance". Internet finance was redefined by the Chinese government in 2018, aiming to use Internet technology to revitalize the financial sector and offset the impact of an economic slowdown. Research shows that major media in China vigorously promote the technological advantages of Internet finance, which improves the potential of the stock market while eliminating potential risks, uncertainties and regulatory constraints. Based on the institutional theory of media research, this study shows that financial news on the new media platform supports the informatization and marketization of the financial sector. This institutional role is a corollary and enabler of China's increasingly financialized economy and culture.